High Internal Phase Oil-in-Water Emulsions Stabilised by Cost-Effective Rhamnolipid/Alginate Biocomplexes - Ilona E. Kłosowska-Chomiczewska; Gabriela Burakowska; Paulina Żmuda-Trzebiatowska; Aleksandra Soukup; Iwona Rok-Czapiewska; Elżbieta Hallmann; Tetiana Pokynbroda; Olena Karpenko; Krystyna Mędrzycka; Adam Macierzanka (Molecules)
A novel, cost-effective, partially purified biosurfactant in the form of a rhamnolipid biocomplex (RLBC) was investigated for its emulsifying properties. The RLBC was obtained through the cultivation of Pseudomonas sp. SP-17 on glycerol, followed by acidic precipitation, without the use of organic solvents for isolation or purification. Composed of rhamnolipids (RLs) and the exopolysaccharide alginate, RLBC exhibited emulsifying properties towards rapeseed oil comparable to those of purified RLs at concentrations as low as 0.15% (w/w), sufficient for the effective stabilisation of oil-in-water (o/w) high internal phase emulsions (HIPEs, 80% oil). Dynamic light scattering analysis revealed similar droplet sizes (9.54 ± 0.96 µm for RLBC vs. 8.93 ± 0.58 µm for RLs), while multiple light scattering confirmed high emulsion stability over 120 days. The emulsions displayed shear-thinning behaviour, with yield stresses of approximately 11.5 Pa and 7.7 Pa for systems prepared with RLBC and RLs, respectively, after seven days of pre-storage. Although increasing the RLBC concentration from 0.15% to 1% (w/w) slightly improved the degree of emulsion dispersion, it did not substantially impact the long-term stability observed at the lowest concentration. Biodegradation tests demonstrated that the RLBC preparations are environmentally friendly alternatives to synthetic surfactants, achieving 60% biodegradation within 2.5 days and complete biodegradation within 14 days, which outperformed synthetic emulsifiers. The RLBC offers both environmental and economic advantages over purified RLs, including reduced production costs and the elimination of organic solvents. Our findings highlight the potential of RLBC for stabilising HIPEs in applications requiring sustainable and biodegradable formulations, such as cosmetics, lubricants, and industrial fluids widely manufactured and utilised today.